2019
DOI: 10.1111/pbi.13258
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of alfalfa forage quality and management through the down‐regulation of MsFTa1

Abstract: Summary Alfalfa (Medicago sativa L.) is one of the most important forage crops worldwide. As a perennial, alfalfa is cut several times each year. Farmers face a dilemma: if cut earlier, forage nutritive value is much higher but regrowth is affected and the longevity of the stand is severely compromised. On the other hand, if alfalfa is cut later at full flower, stands persist longer and more biomass may be harvested, but the nutritive value diminishes. Alfalfa is a strict long‐day plant. We reasoned that by ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 85 publications
0
35
0
Order By: Relevance
“…Several genes related to alfalfa growth, development, and stress resistance appear to have been under selection. For example, MsLOB has been shown to be related to organ development (Zhang et al,2020b); the FT genes MsFTa1 , MsFTa2 , and MsFTc have been confirmed to be involved in flowering time, quality traits, and salt stress (Kang et al, 2019; Lorenzo et al, 2020; Shen et al, 2020), and all genes mapped to regions under selection, suggesting their involvement in adaptation to different geographical environments.…”
Section: Discussionmentioning
confidence: 99%
“…Several genes related to alfalfa growth, development, and stress resistance appear to have been under selection. For example, MsLOB has been shown to be related to organ development (Zhang et al,2020b); the FT genes MsFTa1 , MsFTa2 , and MsFTc have been confirmed to be involved in flowering time, quality traits, and salt stress (Kang et al, 2019; Lorenzo et al, 2020; Shen et al, 2020), and all genes mapped to regions under selection, suggesting their involvement in adaptation to different geographical environments.…”
Section: Discussionmentioning
confidence: 99%
“…However, the CO/COL family was shown to be conserved across species (Griffiths et al, 2003; Wong et al, 2014) and this was also confirmed in alfalfa by the phylogenetic analyses we conducted (Figure S1). FT genes were also shown to be conserved and five of them were characterized in alfalfa and were proven to have functions ( MsFTa1 in particular ) in flowering time control, quality of the forage, fibers and protein content (Lorenzo et al, 2020). For these reasons, we believe proposing a microProtein‐based dominant mutation strategy is relevant not only to undercover the function of the CO/COL family in alfalfa, but also to potentially obtain higher biomass and better quality forage.…”
Section: Microproteins and Mirnas As Promising Targets To Induce Domi...mentioning
confidence: 99%
“…In addition, some of the above flowering-related genes have high functional conservation in different species. Previous research has shown that FT , SOC1 , GI , SVP , and LFY genes can regulate the flowering time of legumes, such as G. max , Medicago truncatula and M. sativa [ 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. However, there are no related reports on the flowering regulatory genes in V. sativa .…”
Section: Introductionmentioning
confidence: 99%